2013
DOI: 10.1021/cs4005002
|View full text |Cite
|
Sign up to set email alerts
|

Promoted Ceria: A Structural, Catalytic, and Computational Study

Abstract: The role of trivalent (La, Sm, Gd, and Y) and tetravalent (Hf, Zr, and Ti) dopants in the catalytic, structural, and electronic properties of ceria was investigated. Promoted ceria catalysts were synthesized by coprecipitation with ammonia and tested in HCl and CO oxidation. Ceria catalysts exhibit a medium high reactivity and excellent stability in HCl oxidation. The intrinsic reactivity of ceria in HCl oxidation can be improved by a factor of 2 when doping with Hf and Zr in appropriate quantities, whereas tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
102
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 100 publications
(118 citation statements)
references
References 72 publications
(127 reference statements)
16
102
0
Order By: Relevance
“…If a catalytic reaction mechanism involves formation and curing of oxygen vacancies in the catalyst, then the rate of the reaction may depend on the number of the volatile oxygen species available, which should lead to a correlation between the reaction rate and the catalyst's OSC. The suggested mechanisms of the HCl oxidation reaction over ceria involve formation of oxygen vacancies in the catalyst [17,53]. In support of this theory, the study [17] establishes the correlation between HCl oxidation activity of differently treated ceria samples and their ultimate reducibility by hydrogen at 573 K (as opposed to the correlation to their surface area).…”
Section: On Oxygen-storage Capacity Of the Electrospun Ceria-zirconiamentioning
confidence: 63%
See 1 more Smart Citation
“…If a catalytic reaction mechanism involves formation and curing of oxygen vacancies in the catalyst, then the rate of the reaction may depend on the number of the volatile oxygen species available, which should lead to a correlation between the reaction rate and the catalyst's OSC. The suggested mechanisms of the HCl oxidation reaction over ceria involve formation of oxygen vacancies in the catalyst [17,53]. In support of this theory, the study [17] establishes the correlation between HCl oxidation activity of differently treated ceria samples and their ultimate reducibility by hydrogen at 573 K (as opposed to the correlation to their surface area).…”
Section: On Oxygen-storage Capacity Of the Electrospun Ceria-zirconiamentioning
confidence: 63%
“…In support of this theory, the study [17] establishes the correlation between HCl oxidation activity of differently treated ceria samples and their ultimate reducibility by hydrogen at 573 K (as opposed to the correlation to their surface area). Teschner and co-workers [53] offer further theoretical insights into the role of oxygen vacancies in the HCl oxidation over ceria: according to the calculations, lower energy of oxygen vacancy formation in the catalyst will facilitate the Deacon reaction if such energy decrease is accompanied by lower energy of chlorine vacancy formation. Calculations of the vacancies formation energies for different doped ceria samples are in good agreement with their HCl oxidation performance: tetravalent metal oxides (Zr, Hf) are beneficial, whereas trivalent metal oxides (La, Sm) are detrimental.…”
Section: On Oxygen-storage Capacity Of the Electrospun Ceria-zirconiamentioning
confidence: 99%
“…Perdew-Becke-Ernzerhof (PBE) [45] functional was used in combination with an effective U term, U eff , of 4.5 eV (this term is defined as the difference between the Coulomb, U, and the exchange, J, terms) [46], as it has been previously proven to provide satisfactory results [47][48][49][50]. The purpose of adding this Hubbard term U is to diminish the self-interaction error and to properly localize the Ce 4f states.…”
Section: Computational Detailsmentioning
confidence: 99%
“…One of the efficient methods to restrain this effect and improve the property of CeO 2 support is incorporating foreign metal cations into the lattice of CeO 2 [15][16][17]. It has been reported that doping of Ti or Sn in CeO 2 can modify the catalyst surface area and insertion of doping ions improve the lattice oxygen mobility, resulting in a better redox quality [18]. Solid solutions of Ce 1−x Ti x O 2 and Ce 1−x Sn x O 2 have been reported by Baidya et al [19] to show high OSC.…”
Section: Introductionmentioning
confidence: 99%